PEMETAAN KAWASAN EKOWISATA SELAM DI PERAIRAN PULAU PANJANG, JEPARA, JAWA TENGAH - Indarjo, Agus (Jurnal Harpodon Borneo, 2014)
This research purposed at determining mapping of waters area Panjang Island for marine ecotourism activities. Data were collected by field survey. Data analysis using by analysis of waters suitability and spatial analysis using GIS. Analysis results of the waters Panjang Island suitability for diving ecotourism activities class suittable at station 3, station 4, station 5, and station 6. Diving ecotourism activities categories class not suitable at station 1, station 2 and station 7. Key words : Diving ecotourism, mapping of waters area, Panjang Island